2011
DOI: 10.5604/15093492.933788
|View full text |Cite
|
Sign up to set email alerts
|

Body posture and syndromes of back pain

Abstract: An incorrect body posture (especially scoliosis) and performance of work-related tasks in non-ergonomic positions increase the probability of back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
(60 reference statements)
1
12
0
1
Order By: Relevance
“…There was no statistically significant difference between the groups in terms of vertebral lean angle [13]. A change in body posture combined with non-ergonomic work affects the emergence of pain, as evidenced by Nowotny et al [14]. The results of these studies also seem to be confirmed in three studies proving that the size of the breasts is associated with pain of the musculoskeletal system [9][10][11].…”
Section: Discussionmentioning
confidence: 79%
“…There was no statistically significant difference between the groups in terms of vertebral lean angle [13]. A change in body posture combined with non-ergonomic work affects the emergence of pain, as evidenced by Nowotny et al [14]. The results of these studies also seem to be confirmed in three studies proving that the size of the breasts is associated with pain of the musculoskeletal system [9][10][11].…”
Section: Discussionmentioning
confidence: 79%
“…Alongside the progress of civilization, cervical spine pain complaints have become an increasingly large therapeutic and epidemiological problem. It is connected with a radical change in the level of physical activity and in lifestyle [1][2][3][4][5]. During the initial phase of these ailments, the feeling of overload of the structures located directly in the nape area prevails.…”
mentioning
confidence: 99%
“…Here, the postural muscles must be active enough to oppose the force of gravity, but not so active as to generate an excessive energy cost. The structure of the human body is such that the postural tension is distributed globally, rather than being focused locally [5,6,8,23,29].…”
Section: Introductionmentioning
confidence: 99%